2021
DOI: 10.37360/blacpma.21.20.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and anti-inflammatory effect of Lippia pedunculosa Hayek essential oil and its β-cyclodextrin inclusion complex

Abstract: Lippia pedunculosa Hayek (EOLp) presents tripanocid and amebicid effects. However essential oil needs to be further studied in experimental models of analgesia and inflammation once the prevalence of pain in the population generates great suffering and disability and the drugs most often used have undesirable side effects. We also evaluated whether the inclusion complex formulation EOLp/β-cyclodextrin (β-CD) was able to improve the antinociceptive activity of the EOLp alone. Data were evaluated by analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…First, motor coordination was assessed by the rota-rod test ( Fajemiroye et al, 2018 ). The rota-rod test is important to ensure that the drug’s antinociceptive effects are not due to neurotoxicity, depression, or non-specific relaxation of the Central Nervous System (CNS), avoiding false-positive results ( Quintans-Júnior et al, 2010 ; Braga et al, 2021 ). Our results showed no changes in motor coordination in mice after ACS-AZ treatment; thus, ACZ-AZ activity in the nociception tests cannot be attributed to myorelaxant or CNS sedative effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, motor coordination was assessed by the rota-rod test ( Fajemiroye et al, 2018 ). The rota-rod test is important to ensure that the drug’s antinociceptive effects are not due to neurotoxicity, depression, or non-specific relaxation of the Central Nervous System (CNS), avoiding false-positive results ( Quintans-Júnior et al, 2010 ; Braga et al, 2021 ). Our results showed no changes in motor coordination in mice after ACS-AZ treatment; thus, ACZ-AZ activity in the nociception tests cannot be attributed to myorelaxant or CNS sedative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal stimulation activates nociceptors (non-myelinated C fibers), which transmit information to specific regions in the CNS, producing an organized nociceptive response ( Sulaiman et al, 2009 ; Mekonnen et al, 2010 ; Singh et al, 2018 ). For this reason, this experimental model is used to assess the effects of opioid, sedative, and hypnotic drugs ( Yeung et al, 1977 ; Braga et al, 2021 ). Similarly to morphine, we observed that ACS-AZ increased the time latency between the contact of the animal’s hind paw with the hot plate and the paw-licking reaction or jumping off the surface.…”
Section: Discussionmentioning
confidence: 99%